2008
DOI: 10.1080/03640210701863396
|View full text |Cite
|
Sign up to set email alerts
|

Observing Tutorial Dialogues Collaboratively: Insights About Human Tutoring Effectiveness From Vicarious Learning

Abstract: The goals of this study are to evaluate a relatively novel learning environment, as well as to seek greater understanding of why human tutoring is so effective. This alternative learning environment consists of pairs of students collaboratively observing a videotape of another student being tutored. Comparing this collaboratively observing environment to four other instructional methods-one-onone human tutoring, observing tutoring individually, collaborating without observing, and studying alone-the results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
180
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(191 citation statements)
references
References 59 publications
7
180
1
3
Order By: Relevance
“…In the present study and previous research by Chi et al (2008), pairs of students solved problems collaboratively as they observed tutoring. This combination of collaborative problem solving and observing tutoring is called collaboratively observing tutoring.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…In the present study and previous research by Chi et al (2008), pairs of students solved problems collaboratively as they observed tutoring. This combination of collaborative problem solving and observing tutoring is called collaboratively observing tutoring.…”
mentioning
confidence: 69%
“…However, the gains of the pairs in the observing tutoring condition were not significantly different from those of the two old conditions (individuals observing tutoring and tutoring). Chi et al (2008) compared human tutoring with observation of human tutoring along with several other control conditions. Their experiment was different from the Craig et al (2004) experiments in several ways.…”
Section: Observational Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies that have investigated example-based learning in the context of collaborative learning yielded somewhat inconsistent results (Chi et al 2008;Craig et al 2009;Kirschner et al 2010;Rummel and Spada 2005;Rummel et al 2009). Kirschner et al showed that learning from "traditional" worked examples on a highly structured task (heredity problems) was more effective when done individually than collaboratively, whereas learning by solving conventional problems was more effective when done collaboratively than individually.…”
Section: For What Kinds Of Tasks Is Example-based Learning Effective?mentioning
confidence: 99%
“…For example, demonstrating that an individual learns more by working in a group than working alone may be attributed to the increase of information exchange and not to the fact that the individual was in a social exchange. Chi et al (2008), recognizing this distinction, proposed that learning from social interaction may be due to the same processes involved in self-explanation (e.g., elaborating on a topic by explaining to oneself).…”
Section: Study 1: the Protégé Effectmentioning
confidence: 99%